Analysis of the yellowfin tuna marketing chain at PPP Pondok Dadap Sendang Biru, South Malang - Andriawan, Soni; Aprilia, Ivony Rosa; Hermawan, David (Universitas Malikussaleh, 2022)
The goal of this study was to investigate the yellowfin tuna marketing chain in PPP Pondok Dadap Sendang Biru. Additionally, this study determined the margin and price share earned by yellowfin tuna fisherman. This research employed a survey strategy that included direct observation and interviews. The data used were original sources collected during October and November 2021. The respondents were chosen using the snowball sampling technique, which is a technique for identifying informants or respondents who possess a wealth of information on the research being conducted. There were 37 respondents. According to the study's findings, there are three distinct channels for yellowfin tuna marketing at PPP Pondok Dadap Sendang Biru. In chain 2, retailers earned the largest overall margin of Rp. 8,864/Kg, or 29 percent. In channel 3, retailers earned the largest overall margin of Rp. 12,000/Kg, or 34%. The biggest Fisherman's share, at 62 percent, is in the type 2 marketing chain.Keywords: fishermans share; marketing chain; margin; tuna